Territorial Disputes and Problem of Border Demarcation of USSR (Russia) and China in 1960-1990 - A. P. Kostyuchenko (Научный диалог)
The article is devoted to problems of Russian-Chinese border demarcation. Russian-Chinese relations, with all its positive dynamics, are characterized by the presence of a number of acute problems, although somewhat moved “by the wayside” because of the more important bilateral priorities, have objectively high “destructive” potential. The research urgency is caused by the fact that the most complex, sensitive and explosive issue, until recently, remained border and territorial issue. Its decision in 2004 was a historic event in Russian-Chinese relations. This problem requires further research into the complex of relations between two great states. It is emphasized that the Soviet-(Russian)-Chinese border disputes are not the new trend of the time. In different historical stages of the Soviet Union the preservation of the existing borders was always important for the structures involved in the solution of border issues. The aim of Soviet government was to preserve the contractual framework, carrying out clarification of the boundary in certain areas, their redemarcation. Since the middle of 1960-ies, the Soviet government approved the conclusion of a new Agreement on the border, its demarcation, with the exception of the Islands near Khabarovsk. In making this decision the representatives of the Central office of the border police took part. The article is devoted to one of the episodes of cooperation with the People’s Republic of China in establishing boundaries.